Formulasi Lilin Aromaterapi Berbahan Aktif Minyak Atsiri Sereh Wangi (Cymbopogon winterianus) dan Jeruk Lemon (Citrus limon): Aromatherapy Candle Formulation with Active Ingredients of Citronella (Cymbopogon winterianus) and Lemon (Citrus limon) Essential Oils - Vika Aura Rislianti; Laode Rijai; Fika Aryati (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Aromatherapy is therapy that uses aromatic compounds to treat, cut or prevent disease, infection, and anxiety by inhaling them. Citronella (Cymbopogon winterianus) and lemon (Citrus limon) have essential oils that work as aromatherapy. The aim of the study was to get aromatherapy candle preparations from essential oils of citronella and lemon. The research was carried out experimentally by making aromatherapy wax preparations from the formulation of stearic acid and paraffin wax with a ratio of 30%: 70% (F1), 40%: 60% (F2) , 50%: 50% (F3), 60%: 40% (F4), 70%: 30% (F5) and adding a combination of citronella essential oil and lemon essential oil in a ratio of 1%: 5% (A1), 2%: 4% (A2), 3%: 3% (A3), 4%: 2% (A4), 5%: 1% (A5), tests of physical stability were performed as burn time and melting point and determination of panellist’s preferences in the form of visual preference, candle aroma before combustion, candle aroma after combustion, detection of candle odor for the first time and perceived therapeutic effect. The best wax base is 60%: 40% (F4) and the best aromatherapy wax formulation is a combination of citronella essential oil and lemon essential oil 4%: 2% (A4) and 5% : 1% (A5) to produce a comfortable and pleasant therapeutic effect.